Clinical evaluation of total and high-avidity anti-dsDNA antibody assays for the diagnosis of systemic lupus erythematosus. (October 2019) - Yuan, W; Cao, H; Wan, P; Shi, R; Zhou, S; Zheng, J
Background: This study evaluated the diagnostic performances of total and high-avidity (HA) anti-dsDNA enzyme immunoassays (EIA) in Chinese systemic lupus erythematosus (SLE) patients. Methods: A total of 410 serum samples from 217 SLE patients, 54 patients with other systemic autoimmune diseases, and 139 healthy subjects were tested on total and HA anti-dsDNA EIA, as well as three commercial in vitro diagnostic kits: BioPlex 2200 ANA Screen, Kallestad anti-dsDNA EIA, and Crithidia Lucilae IFA. The disease activities of SLE patients were assessed using the modified SLE Disease Activity Index. The diagnostic performances of each assay were analyzed using Analyse-it software. Results: The diagnostic performances of the total and HA anti-dsDNA EIA kits were comparable to other commercially available in vitro diagnostic assays. Receiver operating characteristic curve analysis demonstrated an area under the curve ranging from 0.85 to 0.89, with the total anti-dsDNA kit demonstrating the highest sensitivity and the HA kit showing higher specificity. An overall agreement of >90% was observed between the total and HA anti-dsDNA EIA kits and commercially available quantitative anti-dsDNA kits. The ratio of HA to total anti-dsDNA antibody was significantly higher among SLE patients with active disease status and/or kidney damage. All assays exhibited a significant correlation with disease activity and multiple clinical manifestations. Conclusions: While the clinical performances of various anti-dsDNA assays showed adequate agreements, the BioPlex 2200 anti-dsDNA assay demonstrated the highest positive likelihood ratio and odds ratio. The HA anti-dsDNA EIA kit in association with the total anti-dsDNA kit provided superior performance in SLE diagnosis and monitoring disease activity.